2018
DOI: 10.1101/282343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Best Prediction of the Additive Genomic Variance in Random-Effects Models

Abstract: The additive genomic variance, the chief ingredient for the heritability, is often underestimated in phenotypegenotype regression models. Various remedies, including different models and estimators, have been proposed in order to improve on what has been coined the "missing heritability". Recently, debates have been conducted whether estimators for the genomic variance include linkage disequilibrium (LD) and how to explicitly account for LD in estimation procedures.Up-to-now, the genomic variance in random eff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Recent work by Schreck and Schlather (2018) has suggested that the direct estimation of the heritability using REML variance components is biased, so we use their proposed estimator. For the traditional estimates using REML estimates as proposed in a conference presentation by de los Campos (2017), we refer to Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work by Schreck and Schlather (2018) has suggested that the direct estimation of the heritability using REML variance components is biased, so we use their proposed estimator. For the traditional estimates using REML estimates as proposed in a conference presentation by de los Campos (2017), we refer to Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Breeding values are often modeled as additive genetic variance (Holland, Nyquist, & Cervantes-Martínez, 2003;Mrode, 2000). As a consequence, the theoretical upper bound of predictive power in this model is equal to the narrow sense heritability of a given trait (Lourenço, Ogutu, & Piepho, 2019;Schreck, Piepho, & Schlather, 2019). For traits with high heritability, this approach works rather well (Figure 1).…”
Section: Structural Organization Performance Indicators and Analytics For A Breeding Programmentioning
confidence: 95%
“…Estimates of genetic variance from genome-based models pertains to all genotyped individuals, which again does not have a clearly defined time point. In addition, the "genomic variance" is plagued with model "misspecification" (Gianola et al, 2009;de los Campos et al, 2015), see also Schreck et al (2019).…”
Section: Temporal Analysismentioning
confidence: 99%